Seismic behaviour of corroded reinforced concrete beam column joints - Kee, Stella Ding Yue (2019)
Beam-Column Joints are important components in a Reinforced Concrete structure, they are responsible for bringing together the overall structural systems and are critical zones for the transfer of moments and forces between the columns and beams. They are also the most critical and vulnerable link in a structural system that attributes to failure during catastrophic earthquakes, often resulting in partial or complete collapse. On the other hand, one of the main issues in Reinforced Concrete structures is the corrosion of reinforcement. Beam-Column Joints are commonly found in structures that are prone to extreme weathering conditions. Building structures in coastal environment are also very susceptible to corrosion of reinforcement as well. This constant, ongoing corrosion process can reduce the tensile strength of the concrete and causes the overall structure to weaken and eventually fail. This is one of the most prevalent problems that affect the durability of concrete and it is one of the main reasons resulting in early distress of Reinforced Concrete structures. Thus, in this research, Beam-Column Joints under different corrosion levels will be investigated. A total of five full-scale Reinforced Concrete Beam wide Column Joints were designed, constructed, corroded and tested to determine their behavior under cyclic loading. The variables in the test specimens include the type of Joints and the corrosion level of specimens. Exterior and Interior Beam-Column Joints were studied and examined in this research separately. The specimens were aimed to test to the point of axial failure under the application of a constant axial force and lateral cyclic loadings to simulate an actual earthquake. From the experiments, the corrosion rates, hysteresis graphs, crack patterns and displacement results were obtained and using this information, the energy dissipation, rotation, curvature and deformation of the structure were computed and compared.